Exploring challenges faced by parents of children with tuberculosis in Klang and Petaling Districts of Selangor State, Malaysia: A qualitative study / S Maria Awaluddin ... [et al.] - Awaluddin, S Maria; Ismail, Nurhuda; Yasin, Siti Munira; Zakaria, Yuslina; Mohamed Zainudin, Norzila; Kusnin, Faridah; Mohd Yusoff, Mas Ahmad Sherzkawee; Razali, Asmah (Universiti Teknologi MARA Cawangan Selangor, 2020)
Introduction: Parents play an essential role in their children’s tuberculosis (TB) treatment success despite many challenges from the beginning of their children’s symptoms until completion of the TB treatment. The challenges can be described as perceived barriers, according to the Health Belief Model, a theory of behaviour change. This study aims to explore parents’ experiences on the challenges in achieving a successful TB treatment for their child in two districts of Selangor state, Malaysia. Methods: The research was carried out using a phenomenology study design. In-depth interviews were conducted among purposively sampled parents of children with TB disease who have completed TB treatment or still undergoing treatment from MyTB version 2.1, a national TB surveillance database. The collected data was considered as achieving its saturation level if no new themes arise from the latest interviews’ session. The R-based Qualitative Data Analysis (RQDA) package version 0.2-8 was used for the thematic data analysis. Results: The total number of participants in this study was 15 mothers of children with TB disease; 12 (80%) of the children had completed TB treatment. There were six subthemes identified from this study focusing on the theme of multiple challenges, such as health symptoms challenges, TB investigation challenges, personal challenges, healthcare facilities challenges, administration medication challenges, and community challenges. Conclusions: Parents highlighted many challenges during the child’s illness phase, and they should be given adequate education and appropriate support to ensure TB treatment adherence. TB program managers should take action following the relevant parents’ feedback regarding the quality of TB care in a healthcare facility.